A game of fear - Todd, Charles (New York : William Morrow, an imprint of HarperCollinsPublishers, 2022)
Spring, 1921. Scotland Yard sends Inspector Ian Rutledge to the sea-battered village of Walmer on the coast of Essex, where amongst the salt flats and a military airfield lies Benton Abbey, a grand manor with a storied past. The lady of the house may prove his most bewildering witness yet. She claims she saw a violent murder$1 (Bbut there is no body, no blood. She also insists she recognized the killer: Captain Nelson. Only it could not have been Nelson because he died during the war. Everyone in the village believes that Lady Benton$1 (Bs losses have turned her mind$1 (Bshe is, after all, a grieving widow and mother$1 (Bbut the woman Rutledge interviews is rational and self-possessed. And then there is Captain Nelson: what really happened to him in the war? The more Rutledge delves into this baffling case, the more suspicious tragedies he uncovers. The Abbey and the airfield hold their secrets tightly. Until Rutledge arrives, and a new trail of death follows.s
Keywords: Rutledge, Ian (Fictitious character) -- Fiction; Police -- England -- Fiction; Murder -- Investigation -- Fiction; Essex (England) -- Fiction; Detective and mystery fiction; Historical fiction